1975
DOI: 10.1042/bj1500489
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of thyroxine into tri-iodothyronine by rat liver homogenate

Abstract: By using a highly specific radioimmunoassay the formation of tri-iodothyronine by the deiodination of thyroxine was studied in rat liver homogenate. Several observations suggest that the reaction observed is enzymic in nature. Pre-heating the homogenate for 30 min at 56 degrees C completely abolished conversion of thyroxine into tri-iodothyronine; the component of rat liver homogenate responsible could be saturated with substrate; iodotyrosines displayed competitive activity. Between 0 degrees and 37 degrees C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
1

Year Published

1977
1977
1998
1998

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(70 citation statements)
references
References 25 publications
3
66
1
Order By: Relevance
“…Since it was shown that T3 is biologically more potent than T4 [20,21 ] and that there is an extrathyroidal~zonversion from T4 to T3 [22][23][24], there has been speculation as to whether T 3 is the only biologically active thyroid hormone and that T4 might be a more prohormone for T3 [23,25,26]. However, several workers suggested that T4 could have a true biological activity per se [27][28][29].…”
Section: Blocking Effect Of T4 On the Ts Actionmentioning
confidence: 99%
“…Since it was shown that T3 is biologically more potent than T4 [20,21 ] and that there is an extrathyroidal~zonversion from T4 to T3 [22][23][24], there has been speculation as to whether T 3 is the only biologically active thyroid hormone and that T4 might be a more prohormone for T3 [23,25,26]. However, several workers suggested that T4 could have a true biological activity per se [27][28][29].…”
Section: Blocking Effect Of T4 On the Ts Actionmentioning
confidence: 99%
“…The LPO was expressed as nM of MDA formed per hour per mg protein. man and the supernatant was used for the tn vitro assay of 5'-8 activit-v" accordin~ to the method described earlier [16]. The enzyme activity was expresse~ as ng o~'T 3 generated per hour per nag protein.…”
Section: Methodsmentioning
confidence: 99%
“…RIA for the measurement of in vitro generation of T3 in 5-D assay was done according to the method of Visser et al [16].…”
Section: Biochemistryond Molecular Biology Internationalmentioning
confidence: 99%
“…Although the exact mechanism of action of the antithyroid drugs in the thyroid gland is not definitively established, it has been shown that the effect is closely connected to the intrathyroidal metabolism of the drug itself (Taurog, 1976;Nakashima, Taurog & Riesco, 1978). In contrast to this mechanism no evidence has accumulated concerning the molecular way in which PTU acts outside the thyroid gland, although the microsomal fraction of the liver is supposed to be the main target of action (Visser et al, 1975;Hoffken et al, 1976;Chopra, 1977;Chopra etal., 1978). It has been shown in both animal and human studies that the majority of PTU is excreted as a glucuronic acid conjugate, a process which predominantly occurs in the liver (Lazarus et al, 1975;Marchant, Lees & Alexander, 1979).…”
Section: Introductionmentioning
confidence: 99%